Experimental and numerical investigations on continuous pressure drop characteristic of tube-in-tube recuperative heat exchanger for 1.8 K cooler. (September 2021) - Kim, Kyoung Joong; Bae, Junhyuk; Jin, Lingxue; Jeong, Sangkwon; Choi, Yeon Suk
Highlights: A counterflow heat exchanger using a distributed Joule-Thomson (JT) effect is designed, manufactured, and validated by experiment with liquid helium. The additional enthalpy change by the distributed JT effect is calculated based on the experimental data and is determined by the heat exchange process. This paper suggests a performance factor of the distributed JT effect, which indicates the degree of the distributed JT effect. The geometric specifications of advanced heat exchangers are presented for larger additional enthalpy change. Abstract: To examine the benefit of the pressure drop effect in a heat exchanger, we designed and tested the heat exchanger with significant pressure loss in the temperature range between 4.2 K and 1.8 K. The numerical investigation was also carried out to elucidate the effect of continuous pressure drop, namely the distributed JT effect, in the heat exchanger. We verified the numerical simulation model by comparing the calculation results of the heat capacity rates in two-phase flow conditions with the theoretical values obtained by Clausius-Clapeyron relation. The maximum errors are obtained as 18.4% and 17.0% in two experimental cases, respectively. The performance indicator is defined to explicitly represent the distributed JT effect, which is derived as the ratio of the actual enthalpy change by pressure drop to the maximum potential enthalpy change by pressure drop. It is evaluated as 59% and 67% in the two experimental cases, respectively. The relatively small performance indicators obtained in our experiments are caused by the small heat transfer area of the heat exchanger. To increase the performance indicator of the heat exchanger, we propose an advanced heat exchanger with sufficient pressure drop and increased heat transfer area.